Evaluasi Pelaksanaan Pembelajaran Jarak Jauh Dalam Jaringan Mata Kuliah Membaca Bahasa Mandarin - Wikarti, Aprilia Ruby (Program Studi Pendidikan Bahasa Mandarin, Fakultas Bahasa dan Seni, Universitas Negeri Jakarta, 2022)
Abstract: The Covid-19 pandemic has become one of the catalysts for learning models changes around the world, including Mandarin Language Education Study Program Faculty of Languages ​​and Arts, State University of Jakarta also adapted online distance learning.This article focuses on online distance learning evaluation of basic reading skills courses held at PSPBM UNJ. The scopes of this research are the learning media used, technical constraints and efforts to overcome, and how online distance learning affects students motivation.This research uses quantitative and qualitative methods, by conducting surveys, and using qualitative analysis in the discussion. This research instrument is a mixed questionnaire, which is a combination of open and closed questionnaires using google form. Respondents are PSPBM students and lecturers. This research data are information related to media, obstacles and efforts, also motivation.The results of this research are reading skills online distance learning reading skills used several learning media, such Whatsapp, Zoom, Google Classroom, online game applications. The use of learning media encourage lecturers creativity to choose and use appropriate learning models. In addition, online distance learning also demands student independence in learning. There is a student-centered learning model using project-based learning (such as audio/video recordings of reading words, phrases, sentences, texts) and problem-based learning (such as reading comprehension, discussion) which can be implemented in learning reading skills.